Gut Microbiota Mediator Level and Its Relation to Disease Activity in Ankylosing Spondylitis - Nasrallah, Hasan; Altındağ, Özlem; Akaltun, Mazlum Serdar; Bozdayı, Mehmet Akif; Örkmez, Mustafa; Balbal, Elif; Gür, Ali (Archives of Rheumatology, 2025)
Background/Aims: It is known that the intestinal microbiota plays an essential role in developing many diseases. In this study, the relationship between gut microbiota markers and clinical parameters of ankylosing spondylitis and the effect of drugs on gut microbiota markers were evaluated. The aim of this study is to evaluate the composition of the gut microbiota in individuals with ankylosing spondylitis by comparing it with that of healthy individuals to assess the potential effects of microbial alterations on disease pathogenesis and inflammatory response and to identify differences based on treatment methods. Materials and Methods: This study included 76 AS patients diagnosed for at least 2 years, aged between 18 and 65 (38 anti-TNF recipients and 38 nonsteroidal anti-inflammatory drug [NSAID] recipients), and 38 ageand sex-matched healthy volunteers. Detailed clinical evaluations were conducted on patients and volunteers. All patients underwent a systematic clinical evaluation in accordance with the diagnostic and follow-up criteria for ankylosing spondylitis. In this context, the modified Schober test was performed to assess the lumbar flexion range of motion, chest expansion was measured with a tape measure, and cervical and thoracolumbar spinal range of motion was evaluated using a goniometer. Additionally, a detailed peripheral joint examination, including all major and minor joints, was conducted to identify peripheral joint involvement. Relevant areas were also assessed for the presence of enthesitis in terms of tenderness and pain. Sacroiliac joint tenderness was examined through direct palpation and provocation tests. Erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) were measured in patients and volunteers, and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) scores were also calculated and recorded in the patient group. CD14, CTLA4, CXC16, lipopolysaccharide (LPS), and TLR4 levels were measured in serum samples using the enzyme-linked immunosorbent assay method. Results: Bath Ankylosing Spondylitis Disease Activity Index and BASFI scores were significantly higher in the NSAI (Non-Steroidal Anti Inflammatory) recipient group than in the anti-TNF recipient group (P < .05). C-reactive protein and ESR levels were significantly lower in patients who received anti-TNF therapy than those who received NSAI therapy (P < .05). CTLA4, CXC16, LPS, and TLR4 levels were found to be significantly higher in patients receiving NSAI treatment compared to those receiving anti-TNF treatment and the healthy controls (P < .05). There were no significant differences between patients and controls concerning CD14 levels (P > .05). Conclusion: This research observed that CRP and ESR levels and disease activity scores in AS patients who received anti-TNF treatment were lower than those in the NSAID treatment group and even closer to the control group. It was believed that the connection between microbiota markers and clinical and inflammatory markers can indicate the pathogenesis of AS, guide treatment follow-up, and help develop new treatment strategies.